2017
DOI: 10.3389/fmars.2017.00121
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-Based Density Models for Three Cetacean Species off Southern California Illustrate Pronounced Seasonal Differences

Abstract: Managing marine species effectively requires spatially and temporally explicit knowledge of their density and distribution. Habitat-based density models, a type of species distribution model (SDM) that uses habitat covariates to estimate species density and distribution patterns, are increasingly used for marine management and conservation because they provide a tool for assessing potential impacts (e.g., from fishery bycatch, ship strikes, anthropogenic sound) over a variety of spatial and temporal scales. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Speed reductions should reduce risk year‐round, according to the relationship between speed and the probability that a collision is lethal (Conn & Silber, ). The effect of expanding the ATBA between January and June should be evaluated because the line‐transect data used to derive the whale distributions were collected between July and December and studies have found seasonal changes in fin (Scales et al, ) and humpback (Becker et al, ) whale distributions off California. These evaluations should use data collected throughout the Bight to ensure they capture potential seasonal changes in whale distributions and include changes in ship traffic in the Channel and western approach.…”
Section: Discussionmentioning
confidence: 99%
“…Speed reductions should reduce risk year‐round, according to the relationship between speed and the probability that a collision is lethal (Conn & Silber, ). The effect of expanding the ATBA between January and June should be evaluated because the line‐transect data used to derive the whale distributions were collected between July and December and studies have found seasonal changes in fin (Scales et al, ) and humpback (Becker et al, ) whale distributions off California. These evaluations should use data collected throughout the Bight to ensure they capture potential seasonal changes in whale distributions and include changes in ship traffic in the Channel and western approach.…”
Section: Discussionmentioning
confidence: 99%
“…These two systems differ in the specific data used and in assimilation details, but both provide data‐constrained state estimates for our study area. We limited the predictors to those consistent between the two sources (Becker et al, ): sea surface temperature (SST) and its standard deviation sd (SST), calculated for a 3 × 3‐pixel box around the modelling segment mid‐point), mixed layer depth (MLD, defined by a 0.5°C deviation from the SST), sea surface height (SSH) and sd(SSH). A simple offset (+0.035 m) was applied to the near‐real‐time SSH data to match the historical reanalysis dataset, which had a different reference level (Scales et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The first included the full set of dynamic and bathymetric variables (“Model 1”; Table ). These habitat covariates have been used successfully in previous SDMs in the study area (Becker et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…These variables represent surface water mass identity, physical processes such as mixing and upwelling, and bathymetric features that influence prey availability. For each of these, the same variable or a related variable, e.g., mixed layer depth rather than thermocline depth, has been found to be important as a predictor variable in the eastern tropical Pacific or other regions (Forney et al, 2012;Becker et al, 2017).…”
Section: Data Sourcesmentioning
confidence: 99%